PERJANJIAN-PERJANJIAN PEKERJAAN DUA NEGARA (INDONESIAMALAYSIA) DILIHAT DARI SEJARAH, POLITIK DAN PEMERINTAHAN (INDONESIA-MALAYSIA) - Anita Marianata (Professional: Jurnal Komunikasi dan Administrasi Publik, 2015)
Basically, to state an employment agreement is considered valid or not it’s obliged to pay attention to the provisions of article 1320 of the Civil Code. The provisions of the employment agreement at least benefit workers as stipulated in the labor legislation, company regulations, or collective agreements. A revised agreement between the governments of Malaysia and Indonesia provide some benefits for migrant domestic workers but failed to provide some degree of protection related to low wages and high cost of recruitment. A series of violent cases received widespread attention led Indonesia in June 2009 to prohibit new recruitment of domestic workers to work in Malaysia until the new protection is applied. This agreement includes a positive change where workers are allowed to keep their passports instead must submit passports to the employer, and ensure workers to get their weekly rest. But the agreement didn’t stipulate a minimum wage as Indonesia wanted and perpetuates the recruitment fee structures that entrap workers in debt.Keywords: Employment Agreement, History, Politics, GovernmentBasically, to state an employment agreement is considered valid or not it’s obliged topay attention to the provisions of article 1320 of the Civil Code. The provisions of theemployment agreement at least benefit workers as stipulated in the labor legislation,company regulations, or collective agreements. A revised agreement between thegovernments of Malaysia and Indonesia provide some benefits for migrant domestic workersbut failed to provide some degree of protection related to low wages and high cost ofrecruitment. A series of violent cases received widespread attention led Indonesia in June2009 to prohibit new recruitment of domestic workers to work in Malaysia until the newprotection is applied. This agreement includes a positive change where workers are allowedto keep their passports instead must submit passports to the employer, and ensure workers toget their weekly rest. But the agreement didn’t stipulate a minimum wage as Indonesiawanted and perpetuates the recruitment fee structures that entrap workers in debt.Keywords: Employment Agreement, History, Politics, GovernmentPENDAHULUAN